1986
DOI: 10.1002/pdi.1960030411
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hypoglycaemia by Reflocheck

Abstract: The ability of the Boehringer Mannheim Reflocheck® glucose monitor to measure blood glucose concentration precisely and accurately over the whole of the clinically relevant range was examined. Data obtained in the plasma glucose range (4–10 mmol/l) confirm the previously reported good performance of the instrument. However, in the low normal and hypoglycaemic range it consistently overestimated plasma glucose levels by a variable amount, making it unsuitable, except as a screening instrument, for the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…What tests are performed in furtherance of this intention depends largely if not entirely upon the provisional diagnosis made on the basis of the history and physical examination. Home glucose monitoring devices are not suitable for detecting or diagnosing spontaneous hypoglycaemia in the domestic environment (Southgate & Marks, 1986;Fyffe, 1987) and the temptation to use them on the grounds of simplicity should be avoided. They may, however, be very useful in the Accident and Emergency Department as a rapid guide to the need for further blood letting for investigation and/or the intravenous injection of glucose for the relief of symptoms.…”
Section: Prolonged Fast Testmentioning
confidence: 99%
See 1 more Smart Citation
“…What tests are performed in furtherance of this intention depends largely if not entirely upon the provisional diagnosis made on the basis of the history and physical examination. Home glucose monitoring devices are not suitable for detecting or diagnosing spontaneous hypoglycaemia in the domestic environment (Southgate & Marks, 1986;Fyffe, 1987) and the temptation to use them on the grounds of simplicity should be avoided. They may, however, be very useful in the Accident and Emergency Department as a rapid guide to the need for further blood letting for investigation and/or the intravenous injection of glucose for the relief of symptoms.…”
Section: Prolonged Fast Testmentioning
confidence: 99%
“…Many blood glucose methods that are adequate for monitoring diabetes are insufficiently sensitive, precise or accurate in the hypoglycaemic range to be used for making a definitive diagnosis and should be employed only for screening (Southgate & Marks, 1986).…”
Section: Nature Of the Blood Samplementioning
confidence: 99%
“…There have been no studies comparing visual and meter methods in routine ward use. Two surveys examining the accuracy of visually read BM 1-44 test strips (BCL Boehringer Corporation, London) both reported that approximately one-third of the nurses' readings were greater than one colour block away from the blocks immediately adjacent to the laboratory result (this would mean a minimum error of >25%); 4 to 5% of the tests were considered inaccurate enough to lead to an inappropriate clinical decision (Refs 15,16). Although not directly comparable, these results are no worse than those of similar studies in which meters were used (Refs 12,13).…”
Section: Visual or Meter Read Strips?mentioning
confidence: 99%
“…However, when these devices are evaluated, the lower range of glucose concentrations is not always tested adequately because blood samples in the hypoglycemic range occur infrequently in usual clinical situations. One study that specifically tested the hypoglycemic range found that despite an overall consistency between measurements with a particular device and a reference method, at low glucose concentrations the same relationship did not exist (3). In this study we evaluated a newly introduced glucose measuring device, HemoCue, using a large number of plasma glucose measurements in the hypoglycemic range.…”
mentioning
confidence: 93%